(untitled) (World Economics and Finance Bulletin, 2026)
The relationship between artificial intelligence and financial data quality used for planning budgets, and their role in enhancing the efficiency of external control of commercial banks, is presented in this study. This research assumes that technologies of artificial intelligence are modern tools representing a revolution in the banking work environment due to its contributions to data analysis, processing huge financial records, and presenting exact forecasts to let banks make more realistic and flexible budgets. The theoretical framework showed that artificial intelligence would enhance the capability of accuracy, speed, and reliability of financial data because of reliance on machine learning systems, deep learning, and big data processing. Field analysis in the commercial bank has shown that employees recognize the importance of these technologies in reducing errors, improving the quality of financial reports, and reflecting a positive attitude toward digital transformation